Understanding Childcare Choices amongst Low-Income Employed Mothers in Urban and Rural KwaZulu-Natal - Mbokazi, Nonzuzo (Department of Sociology, 2021)
This study explains how low-income employed mothers navigate care strategies for their young children (0-4 years). The study considers the constraints within which they make ‘choices' about caring for their children using the market, kin and state. In addition, the study argues that these ‘choices' are immensely constrained and that the low-income employed mothers have no real choice. For many women, the ‘feminisation of the workforce' – the growing number of women in paid work – has entailed enormous stress and pressure, as they combine strenuous paid work with the demands of mothering. Low-income employed mothers must balance paid with unpaid work, in ways that are different to women who have more resources. This study analyses how women do this within households where gendered roles and a gender hierarchy continue to prevail. In some cases, low-income employed mothers must take on not only do the ‘work' of managing the household but also the additional ‘work' of soliciting the fathers for financial support and involvement in at least some aspects of their children's lives. This is a phenomenon that existing literature has not captured. The work performed by low-income employed mothers is shaped by changes in the family structure and kinship relations. The family structure in South Africa has been described as disintegrating and in crisis. I argue that the presence of paternal kin had traditionally been a pertinent one in the life of a child (specifically in KwaZulu-Natal, the study site) based on patrilineal belonging. This has significantly shifted and has implications for low-income employed mothers already stretched thin balancing work and childcare with limited support. The ‘choices' made by working women are also framed by their understanding of motherhood, which are in turn framed by cultural and societal expectations and perceptions. Having engaged with the balance between paid and unpaid work (and other forms of work – cognitive work and the work of chasing money and involvement) that the mothers must do (mothering practices), the thesis makes sense of Zulu ideals about motherhood, and how these have shaped and informed the experiences of the mothers, in the present context of the changing position of women. Mothers are nearly always the gatekeepers for the provision of care for children. This study uses the lived experiences of low-income employed mothers to show that they cannot exercise much choice in determining how to provide care for their preschool children. Most of the institutional options – both through the market and the supposed state – are constrained by their inability to afford to look for better options and by their lack of time to travel to better options. Familial or kin options are constrained by the ambivalence of kin and mothers' own expectations and understandings of their own roles. The result is that employed mothers are often on their own, piecing together a combination of childcare arrangements that is very far from the ideal childcare they would like to provide for their children. Low-income employed mothers need to be supported in their roles as employed mothers; this would be possible through subsidized public provision of quality early childhood services. However, policy implications of this would need to be considered. For instance, what would quality childcare provision cost the state? Is it feasible in a country still working on undoing the policy implications of the apartheid state? It could be that the state might not have the capacity to organize this. The South African state has a very poor track record in converting public expenditure into high quality public services. Lessons from this can be drawn from a few examples, for instance health care, education and housing (which are problematic). This thesis adds to the literature in using the lived experiences of employed mothers to show that neither the state nor the market nor kin provide an adequate safety net for the care of the children of low-income employed mothers.